The Influence Of Employee Engagement On Employee Performance And Company Performance At Pt. Bank Negara Indonesia (Persero) Tbk. - Putra Pertama, Jibril; Indiyati, Dian (International Journal of Science, Technology & Management, 2025)
The purpose of this study is to examine employee engagement, employee performance, and financial performance at BNI, as well as to determine the influence of employee engagement on employee performance and financial performance, both partially and simultaneously. This is a quantitative study with verification approach. The research instrument used is a questionnaire employing a Likert scale. The collected data were analyzed using Partial Least Squares (PLS) to test the relationships between latent variables. The PLS method was chosen due to its ability to analyze data with a moderate sample size and without requiring the assumption of data normality. Based on a literature review and preliminary survey results, this study proposes three hypotheses: first, there is a relationship between the level of employee engagement and employee performance at BNI; second, employee performance influences company performance; and third, employee engagement affects company performance.